2014
DOI: 10.1128/jcm.01198-14
|View full text |Cite
|
Sign up to set email alerts
|

Time to Positivity and Detection of Growth in Anaerobic Blood Culture Vials Predict the Presence of Candida glabrata in Candidemia: a Two-Center European Cohort Study

Abstract: cThis study shows the accuracy of exclusive or earlier growth in anaerobic vials to predict Candida glabrata in a large series of candidemic patients from two European hospitals using the Bactec 9240 system. Alternatively, C. glabrata can be predicted by a time to positivity cutoff value, which should be determined for each setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 13 publications
2
17
2
Order By: Relevance
“…We observed a significantly prolonged TTP in the fungemia with C. glabrata as described in the previous studies [9][10][11].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We observed a significantly prolonged TTP in the fungemia with C. glabrata as described in the previous studies [9][10][11].…”
Section: Discussionsupporting
confidence: 88%
“…This succeeded to advocate its presence more frequently and even faster in the anaerobic bottles than in the aerobic ones. A previous study using BACTEC 9240 system demonstrated this feature which distinguished fungemia of C. glabrata with more than 90% of specificity and negative predictive value, but 33% of sensitivity using only the criteria of earlier growth in the anaerobic bottles [9]. In our study, it was not highly sensitive (38.8%) to presume C. glabrata using the same criteria, either.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Individually, C. glabrata accounted for 34.5%, C. albicans accounted for 30.6%, and C. parapsilosis accounted for 8.9% of the clinical isolates. An interesting observation was that C. glabrata was the yeast species present in 85.4% (35/41) of the clinical anaerobic bottles studied, a finding in agreement with a recent publication documenting exclusive or earlier growth of C. glabrata in anaerobic vials in a large series of candidemic patients from two European hospitals (33).…”
Section: Resultssupporting
confidence: 77%
“…The prevalence of C. glabrata in bloodstream infections could be underestimated due to methodological reasons as some isolates of C. glabrata may grow in culture under anaerobic conditions only . In addition, if C. glabrata grows under aerobic conditions, it does so more slowly than other Candida species In an investigation done by Hui et al .…”
Section: Epidemiologymentioning
confidence: 99%